Determinasi Kepatuhan Wajib Pajak Orang Pribadi Dengan Sanksi Perpajakan Sebagai Moderasi - Siringoringo, Molkend; Siringoringo, Whereson (Akuntansi dan Manajemen, 2025)
This study to be focuses on obtaining empirical evidence on the level of taxpayer compliance influenced by several factors consisting of mandatory awareness, tax socialization and implementation of e-filling. This study was conducted using 180 questionnaires distributed to all taxpayers registered at the Pratama Tax Service Office in Bekasi City via WhatsApp. This study uses PLS SEM version 3.0 to process questionnaire data. Based on the test results, it was found that Taxpayer Awareness and E-filing Implementation have a positive and significant effect on taxpayer compliance, while Tax Socialization has a positive but insignificant effect on taxpayer compliance. Tax sanctions are unable to moderate the effect of Taxpayer Awareness and Tax Socialization on taxpayer compliance, while Tax Sanctions are able to moderate the effect of E-filing Implementation on taxpayer compliance, in addition there are several differences with previous studies. Among them are the variables used and the location of the research site.